Prognostic value of myeloid-derived suppressor-like cells in acute myeloid leukemia: insights from immunophenotyping and clinical correlations - Sant’Ana, Alexia N.; Dias, Camila K.; Nunes, Vitória B. S.; Farias, Mariela G.; Alegretti, Ana P.; Portela, Pâmela; Calvache, Ebellins T.; Meirelles, Maria F.; Daudt, Liane E.; Michalowski, Mariana B.; Paz, Alessandra A.; Figueiró, Fabrício (Immunologic research, 2025)
Myeloid-derived suppressor cells (MDSCs) are a heterogeneous population that acts on both innate and adaptive immunity, fostering immune escape in tumors and contributing to cancer progression. Despite the lack of definitive markers for immunophenotyping MDSCs, particularly the polymorphonuclear (PMN-MDSC) subset, these cells seem to play a crucial role in acute myeloid leukemia (AML) patients’ prognosis. Additionally, the maturation stage of MDSCs remains a subject of debate and is largely unknown within the AML context. In this study, we conducted a retrospective analysis of flow cytometry immunophenotyping data obtained at the diagnosis of AML patients. We explored how the enrichment of neutrophil maturation stages, the frequency of PMN-MDSC-like cells and monocytic MDSC-like population (M-MDSC-like), and the ratios of MDSC-like cells to T lymphocytes correlate with relevant prognostic indicators. Our findings revealed that CD45 + CD33 low HLA-DR − CD36 + PMN-MDSC-like cells and mature CD13 + CD11b + CD10 + neutrophils correlate poor survival in AML patients. Furthermore, PMN-MDSC-like cells, and their ratio to T lymphocytes, are elevated in patients with adverse-risk stratification. Similarly, the M-MDSC-like population is increased in FLT3 -ITD mutation carrier patients. Notably, we observed confirmational evidence of CD36 relevance in the AML context, which has emerged recently as a potential marker for PMN-MDSCs. Our study highlights significant findings associating increased MDSC-like subsets and poor prognostic factors in AML.